2021
DOI: 10.7759/cureus.19719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodiafiltration Versus Hemodialysis on Cognitive Function Among Patients With End-Stage Renal Disease: A Multicenter Study

Abstract: Background: Cognitive impairment (CI) and dementia are common in patients with end-stage renal disease (ESRD) undergoing hemodialysis. Their cause is multifactorial. Our study is first to compare the impact of hemodialysis (HD) and online hemodiafiltration (HDF) on patients’ cognitive outcomes. Methods: This was a cross sectional, multicenter cohort study. Adult ESRD patients aged >18 years on regular high flux HD or online HDF were recruited in the study. Clinical, laboratory, daily activities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…These include improvements in the social, physical, and professional domains, characterized by reduced fatigue, joint pain, stiffness, cramp frequency, pruritus, and episodes of hypotension [ 153 , 154 ]. However, current evidence does not support the significant improvement in cognitive function or in the physical and mental health domains with HDF [ 151 , 155 ]. The HDFit trial showed a mild improvement in physical activity, as reflected by higher step counts in patients treated with HDF [ 152 ].…”
Section: Impact Of Hemodiafiltration On Clinical Outcomesmentioning
confidence: 99%
“…These include improvements in the social, physical, and professional domains, characterized by reduced fatigue, joint pain, stiffness, cramp frequency, pruritus, and episodes of hypotension [ 153 , 154 ]. However, current evidence does not support the significant improvement in cognitive function or in the physical and mental health domains with HDF [ 151 , 155 ]. The HDFit trial showed a mild improvement in physical activity, as reflected by higher step counts in patients treated with HDF [ 152 ].…”
Section: Impact Of Hemodiafiltration On Clinical Outcomesmentioning
confidence: 99%
“…15 The actual body of evidence fails to demonstrate a real improvement in cognitive function or physical or mental fitness when comparing OL-HDF versus HD. 47 However, these findings may strongly depend on the length of follow-up, as significant improvement in the various HRQoL aspects might not be achieved in short periods. The few studies that have assessed postdialysis fatigue and recovery time from dialysis treatment did not report a significant association between dialysis modalities and prevalence or severity of fatigue 48,49 or differences in recovery time.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
“…The actual body of evidence fails to demonstrate a real improvement in cognitive function or physical or mental fitness when comparing OL‐HDF versus HD 47 . However, these findings may strongly depend on the length of follow‐up, as significant improvement in the various HRQoL aspects might not be achieved in short periods.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%